Respuesta :

Option C:  [tex](6^{-4})^{-4}[/tex]

Option D:  [tex](6^{-2})^{-8}[/tex]

Option F:  [tex](6^8)^2[/tex]

Solution:

Given expression: [tex]6^{16}[/tex]

To find which expression is equivalent to the given expression.

Let us solve this using exponent rule: [tex]\left(a^{b}\right)^{c}=a^{b c}[/tex]

Option A: [tex](6^{0})^{16}[/tex]

[tex](6^{0})^{16}=6^{0 \times 16}= 6^0[/tex]

It is not equivalent expression.

Option B: [tex](6^8)^8[/tex]

[tex](6^{8})^{8}=6^{8 \times 8}= 6^{64}[/tex]

It is not equivalent expression.

Option C:  [tex](6^{-4})^{-4}[/tex]

[tex](6^{-4})^{-4}=6^{(-4 )\times (-4)}= 6^{16}[/tex]

It is equivalent expression for the given expression.

Option D:  [tex](6^{-2})^{-8}[/tex]

[tex](6^{-2})^{-8}=6^{(-2) \times (-8)}= 6^{16}[/tex]

It is equivalent expression for the given expression.

Option E:  [tex](6^{-1})^{16}[/tex]

[tex](6^{-1})^{16}=6^{(-1) \times 16}= 6^{-16}[/tex]

It is not equivalent expression.

Option F:  [tex](6^8)^2[/tex]

[tex](6^{8})^{2}=6^{8 \times 2}= 6^{16}[/tex]

It is equivalent expression for the given expression.

Hence [tex](6^{-4})^{-4}, \ (6^{-2})^{-8}, \ (6^8)^2[/tex] are the equivalent expressions.

Option C, Option D and Option F are correct answers.

ACCESS MORE